PENGARUH KUALITAS PELAYANAN DAN LOKASI USAHA TERHADAP KEPUASAN KONSUMEN PADA MONA PLAZA HOTEL PEKANBARU - Agustariyani "; Meyzi Heriyanto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
This research was conducted at Mona Plaza Hotel Pekanbaru located at Jalan HR. Soebrantas Km, 18. Pekanbaru, Riau. The purpose of this study was to determine the effect of service quality and business location on consumer satisfaction at Mona Plaza Hotel Pekanbaru partially and simultaneously. In this research the method used is quantitative descriptive analysis with SPSS program. The population in this study were all visitors staying at the Mona Plaza Hotel Pekanbaru in the last year of 2018 totaling 16,789 people. Where the samples in this study were Mona Plaza Hotel Pekanbaru consumers as many as 100 respondents. To determine the sample using the slovin formula. Data collection techniques through interviews and questionnaires, types and sources of data using primary data and secondary data, measurement techniques using a Likert scale.            From the analysis of data which includes validity, reliability, simple linear analysis, multiple linear analysis, determination analysis and significance test with t test (partial test), and F test (simultaneous). The results of this study indicate that the results of the first t test hypothesis testing, service quality on consumer satisfaction is t arithmetic (11,010) > t table (1,6605) means that service quality has a significant effect on consumer satisfaction. Second, business location on consumer satisfaction is t arithmetic (12,184) > t table (1,6605) means that business location has a significant effect on consumer satisfaction. F test Results of service quality have a significant effect on consumer satisfaction, namely F arithmetic (84,412) > F table (3,09). This means that service quality and business location simultaneousely have a significant effect on consumer satisfaction at Mona Plaza Hotel Pekanbaru. Keyword : Service Quality, Business Location, Consumer Satisfaction